Nutritional Value and Inhibitory Activity Αlpha-Amylase of Cookies Made from Addition of Mulberry Leaf and the Extract - Sayuti, Kesuma; Permata, Deivy Andhika; Anggraini, Tuty (Pakistan Journal of Nutrition, 2013)
Utilization of mulberry leaves have the potential ability to be developed, especially for diabetics group. From the previous research proved that mulberry leaf extract and the instant powder had inhibitory activity against alpha-glucosidase enzyme. In this study, it had been observed the nutritional value and alpha-amylase inhibitory activity on cookies made from addition of Mulberry leaf and the extract. The formulation of the cookies using "trial and error". The treatment used is the addition of mulberry leaves (10, 20 and 30%) and the addition of the extract (10, 20 and 30%). The collected data were sensory evaluation, nutritional value, tannins and inhibitory activity against alpha-amylase enzyme. The results showed that Mulberry leaf addition up to 20% and the extract addition up to 30% were acceptable by the panelist. The cookies contain: 3.19%±0.11 up to 3.64%±0.03, moisture content, 2.63%±0.04 up to 2.94%±0.01 ash content, 6.75%±0.37 up to 8.41%±0.42 protein content, 9.54%±0.73 up to 15.27%±0.74 fat content, 71.26%±0.86 up to 76.42%±0.98 carbohydrate, 0% up to 2.40%±0.15 tannin. Inhibitory activity alpha-amylase on cookies made from mulberry leaf extract 10, 20 and 30% were 46.56%±0.94; 95.57±0.25% and 75.74%±0.82, respectively. Inhibitory activity alpha-amylase on cookies made from mulberry leaf 10, 20 and 30% were 50.82%±0.47; 76.89±0.57% and 48.96%±0.70, respectively.